AN ANALYSIS OF FLOUTING MAXIMS IN ”COCO” MOVIE - Kori Amaliah Puji Rohmanti; Bayu Garna Pradika (IKIP Siliwangi, 2018)
This research aim to analyze the maxim flouting that were flouted by the characters in the Coco movie script based on Grice’s cooperative principle. This research used descriptive qualitative method to support in analyzing the data. The data sources of this research were the coco movie and its script. The data were accumulated by downloading the Coco movie and script, watching the movie, and collecting the data from the script. The data analysis was conducted by organizing the data into narration, analyzing the data, and make the conclusion. The result of this research showed what types of maxim were flouted in the movie. The results of this research show that the maxim flouted 11 times in the whole dialogue of the movie. The maxim quantity flouted 5 times or 45%. The maxim of relation flouted 3 times or 27%. The maxim of quality flouted 1 times or 10%. The maxim of manner flouted 2 times or 18%. The most dominant maxim flouting is quantity maxim flouting.Keywords: Cooperative principle, Flouting Maxim, Coco Movie